RANCANG BANGUN ANTENA YAGI MODIFIKASI DENGAN FREKUENSI 2,4 GHZ UNTUK MENINGKATKAN DAYA TERIMA WIRELESS USB ADAPTER TERHADAP SINYAL WIFI - ., Slamet Triyadi (Faculty of Engineering, Universitas Tanjungpura, 2017)
Wireless communication systems need the role of antenna in a data transmission process. Waves electromagnet acceptable and transmitted because of antenna. An antenna good quality make received information quality more bettter. In this research, the writer build a yagi antenna is modified at a frequency of 2,4 GHz to increase the receive power of wireless USB adapter for Wifi Signals. Yagi antenna modification test done to the distance 75 meters and 100 meters. The average of received signal power for ten times experiment are -73,15 dBm at 75 meters and -79,1 dBm at 100 meters. Besides, the average of received signal power of reference antenna (omni antenna, the default setting of wireless USB adapter) are -87,8 dBm at 75 meters and cannot be detected at 100 meters. The comparison from yagi antenna modification and reference antenna is the gain of yagi antenna modification. The values are 17,65 dBm at 75 meters and 23,9 dBm at 100 meters. In terms of the gain, yagi antenna modification is succesful made to its purpose which is to increase the receive power of wireless USB adapter for Wifi Signals. Â Keywords : Yagi Antenna, Signal Strength, WIFI , Wireless USB Adapter, Antenna Yagi Modifikasi